Acute macular neuroretinopathy and COVID-19 or SARS-CoV-2 infection: case report and literature review - Wang, Xing; Wang, Peng; Lu, Jing; Ju, Huan; Xie, Hao; Peng, Hui (Frontiers in Medicine, 2024)
Purpose To describe a case of acute macular neuroretinopathy (AMN) associated with COVID-19 infection and a related literature review. Methods A case from the First Affiliated Hospital of Chongqing Medical University was reported that could be linked to COVID-19 or SARS-CoV-2 infection. We performed a comprehensive search on PubMed, retrieving articles containing information on AMN after COVID-19 or SARS-CoV-2 infection. The key words used were ‘COVID-19’, ‘SARS-CoV-2’, ‘ophthalmic manifestations’, ‘acute macular neuroretinopathy’, and ‘paracentral scotomas’. The relevant data were extracted, charted, consolidated, and evaluated. Moreover, manual exploration of the reference lists of pertinent articles was carried out. Results We describe the case of a 30-year-old young woman who developed bilateral AMN one day after being infected with COVID-19 or SARS-CoV-2. She had severe visual impairment (20/2000 OD and 20/32 OS), and her vision recovered after taking oral corticosteroids. After reviewing the literature, we summarized 16 relevant reports and found that symptoms of AMN tend to arise 1 day to 1 month after COVID-19 or SARS-CoV-2 infection. Contraceptive pills and other risk factors should be avoided to reduce the risk of adverse outcomes. Oral prednisone may be an effective treatment for those experiencing important vision loss. Conclusion Symptoms of AMN can arise 1 day to 1 month after COVID-19 or SARS-CoV-2 infection. Ophthalmologists should remain vigilant about this disease, notably because patient characteristics may deviate from the norm.